The ontological politics of evidence and policy enablement. Issue 3 (4th May 2018) - Carusi, F. Tony; Rawlins, Peter; Ashton, Karen
Abstract: Ontological politics has received increasing attention within education policy studies, particularly as a support for the notion of policy enactment. While policy enactment offers serious challenges to traditional approaches toward policy implementation, this paper takes up ontological politics as a concept that extends beyond implementation and holds consequences for policy formation as well. Analysing the different uses of evidence in recent policy documents from Aotearoa New Zealand, this paper argues that an ontological politics of evidence grounds policies in ways that define what can and cannot be enacted, what this paper terms policy enablement. The analyses illustrate an ontological politics of evidence that excludes non-experts in the first instance, and that sanitises the critical elements of enactment in the second. Both analyses highlight the ways policy enablement emerges from ontological politics and offers a supplement to policy enactment. Following these analyses, the paper offers some provisional thoughts on the relationship between enablement and enactment as an approach that attends to context as a constitutive element of policy-making.